Physicochemical and sensory properties of juice from different types of date - Tipvarakarnkoon, Tatsawan; Burapalit, Kittanan; Kitsawad, Kamolnate (Food and Applied Bioscience Journal, 2020)
The date palm juice was made from different level of ripening and grading of date palm fruits (fresh date, premature fruit drop, and dried date). This study focused on the physiochemical and sensory properties of developed pasteurized date juice, total soluble solid (TSS), pH, color, opacity, overall yield from date pulp, and yield by filtration of pasteurized date juices. Fifty consumers were asked to rate the intensity and their liking products using rate−all−that−apply (RATA). The pasteurized date juices with different date fruits were produced by adjusted at the same TSS at 10.5°Brix of final juices. The results revealed that the initial total TSS of date juice and overall yield increased conversely the pH, color (L*) and opacity of date juice by stage of ripening of date fruit. Premature fruit drop juice was bright in color but cloudy. Lesser overall yield than dried date juice, but comparable to fresh date juice has been found. Among all, the flavor intensity of premature fruit drop was higher than others. Even though the physicochemical and sensorial characteristics of juices were different, the consumer preference was comparable with different date fruits.